1998
DOI: 10.1002/(sici)1099-1077(1998110)13:2+<s98::aid-hup54>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Residual effects of evening and middle-of-the-night administration of zaleplon 10 and 20 mg on memory and actual driving performance

Abstract: Zaleplon, a new pyrazolopyrimidine hypnotic, possesses an unusually short elimination half-life (ca 1 h). This study was conducted to determine whether middle-of-the-night administration of zaleplon aects memory or driving performance the following morning. Twenty-eight healthy volunteers participated in a double-blind, 7-way, crossover study. They ingested capsules twice on each treatment night; once before initiating sleep and again after being brie¯y awakened 5 h later. Treatments were: placebo at both time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(23 citation statements)
references
References 18 publications
(14 reference statements)
1
22
0
Order By: Relevance
“…Ten studies [10][11][12][13][14][15][16][17][18] (labeled Study 1-10 in the text and Tables) were identified that met all inclusion criteria for the meta-analyses. Study characteristics are summarized in Table 1.…”
Section: Selected Studies and Subjectsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ten studies [10][11][12][13][14][15][16][17][18] (labeled Study 1-10 in the text and Tables) were identified that met all inclusion criteria for the meta-analyses. Study characteristics are summarized in Table 1.…”
Section: Selected Studies and Subjectsmentioning
confidence: 99%
“…Six studies [10][11][12][13][14] (Study 1-6) were performed in the 1980s and examined the effects of benzodiazepines and zopiclone after two nights of bedtime administration. Three studies [15][16][17] (Study 7-9) examined the effects of zopiclone, zolpidem and zaleplon after one night of bedtime administration. Two studies [16,18] (Study 8 and 10) also examined zolpidem and zaleplon after middle-of-the-night administration.…”
Section: Selected Studies and Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, Troy, Lucki, Unruh, Cevallos, Leister, Martin, Furlan, and Mangano (2000) showed no significant performance differences between placebo and 10-mg zaleplon 1.25 hours post-dose. However, Vermeeren, Danjou, & O'Hanlon (1998) found a significantly degraded memory effect at 6.5 hours after a single dose administration of both 10-mg and 20-mg zaleplon. Allen, Curran, & Lader (1993), tested normal participants after a 20-mg dose of zaleplon and found most performance at 3-hrs post-dose to be "generally similar to performance on placebo."…”
Section: Is Subject Terms Introductionmentioning
confidence: 99%